Carryover of ACCase inhibitors for corn - Dalpubel Mattiuzzi, Mateus; Nalin, Daniel; Inojosa Ferreira, Luiz Augusto; Placido, Henrique Fabrício; Biffe, Denis Fernando; Silvério De Oliveira Junior, Rubem (Revista Ceres, 2023)
Sequential crops may be affected by herbicide residuals in the soil. In corn crop there are reports of problems when the crop is sown soon after application of ACCase-inhibiting herbicides. The aim of this study was to evaluate safety intervals for the application of ACCase-inhibiting herbicides before sowing corn in different soils. Two experiments were conducted in a greenhouse, and in the field conditions. In both, the experimental design were completely randomized in factorial scheme 6x4+1 (6 periods of application x 4 herbicides + 1 control) with five replications. The treatments were: haloxyfop-P-methyl (124.7 g ha-1), clethodim – formulation 1 (192 g ha-1), quizalofop-P-ethyl (100 g ha-1) and clethodim formulation 2 (192 g ha-1) in applications at 15, 10, 5, 3, 1 and 0 days before sowing in sandy and clayey soil. In the greenhouse, formulations based on clethodim were more safety in both types of soils, and safety intervals for clethodim-based herbicides were 5 days and greater than 15 days for quizalofop-P-ethyl and haloxyfop. Haloxyfop should not be applied on day of sowing in clay soil. In the field none of the treatments compromised the development and yield of the crop, even when applied on the day of sowing.